Boundary Extraction and Vessel Width Calculation in Retinal Fundus Images - Manjunatha, R.; Sheshadri, H. S. (Asian Journal of Engineering and Applied Technology, 2019)
A retinal vessel width measurement algorithm is presented towards ROP (Retinopathy of Prematurity) plus diagnostic automation. The algorithm involving geometrical feature extraction with the image processing is used to compute the effective width of the major vessels in a retinal image. Width measurement is shown to be a statistical parameter estimation related to the statistics of the retinal information. The algorithm is applied to the generic data bases available and the results are found to be satisfactory with ophthalmologist opinion. The effectiveness of the algorithm depends on the fundus image capturing settings.